Effect of number of oocytes and embryos on in vitro oocyte maturation, fertilization and embryo development in bovine - Salvador, I. (2011)
Fil: Salvador, I. Centro de Tecnología Animal. Instituto Valenciano de Investigaciones Agrarias (CITA-IVIA). Apdo. 187, 12400 Segorbe (Castellón), Spain.